Ferroelectric properties of Pb(Zr1/2Ti1/2)O3-Pb(Zn1/3Nb2/3)O3 ceramics under compressive stress - Yimnirun R. (2014)
Effects of compressive stress on the ferroelectric properties of ceramics in PZT-PZN system were investigated. The ceramics with a formula (1-x)Pb(Zr1/2Ti1/2)O3-xPb(Zn1/3Nb2/3)O3 or (1-x)PZT-(x)PZN (x = 0.1-0.5) were prepared by a conventional mixed-oxide method. The ferroelectric properties under the compressive stress of the PZT-PZN ceramics were observed at the stress levels up to 170 MPa using a compressometer in conjunction with a modified Sawyer-Tower circuit. It was found that with increasing compressive stress the area of the ferroelectric hysteresis (P-E) loops, the saturation polarization (Psat), the remnant polarization (Pr), and the coercive field (Ec) decreased. These results were interpreted through the non-180° ferroelastic domain switching processes. © 2008 Elsevier B.V. All rights reserved.